Association between composite dietary antioxidant indices and anemia: NHANES 2003-2018. - Qian Wu; Zhiyu Wang; Jieyu Xia; Hui Xu; Gang Huang; Guangyong Feng; Xiaoxia Gou (PLoS ONE)
Background There is increasing acknowledgment of the potential role that diet rich in antioxidants may play in the prevention of anemia. As a significant indicator of antioxidant-rich diet, the relationship between the composite dietary antioxidant index (CDAI) and anemia has not been extensively studied. Therefore, this study aims to explore the association between CDAI and anemia. Methods Utilizing datas from the 2003-2018 National Health and Nutrition Examination Survey (NHANES) database. The CDAI was calculated using six dietary antioxidants, based on two 24-hour dietary recall interviews, serving as comprehensive measure of the intake of these antioxidants. Weighted multivariable logistic regression and restricted cubic spline (RCS) analysis was conducted to investigate the association between CDAI and anemia. Furthermore, subgroup analyses were performed to enhance datas reliability. Results A total of 33914 participants were included in the study, among which 3,416 (10.07%) were diagnosed with anemia. The unadjusted model showed negative association between CDAI and anemia (odds ratio [OR]: 0.94; 95% confidence interval [95%CI]: 0.93-0.96; P < 0.001). After adjusting for all covariates, with each increase in CDAI level linked to 3% lower risk of anemia (OR: 0.97; 95%CI: 0.95-0.98; P < 0.001). Moreover, when CDAI was categorized into quartiles, the observed trend persisted (P < 0.001). The RCS analysis revealed linear negative relationship between CDAI and anemia (P for nonlinearity = 0.619). Except for sex, smoking, diabetes and hypertension, no statistically significant interactions were found in any subgroup analysis (P < 0.05 for interaction). Conclusion Our findings suggest that CDAI levels are inversely related to the prevalence of anemia. Consequently, monitoring individuals with low CDAI scores may facilitate the timely identification of anemia and enhance clinical decision-making.